Photonics-based mid-infrared interferometry: The challenges of polychromatic operation and comparative performances - Tepper, Jan; Diener, Romina; Labadie, Lucas; Minardi, Stefano; Gross, Simon; Arriola, Alexander; Withford, Michael; Nolte, Stefan (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
This paper is one of a three-part series of papers on photonics-based mid-IR interferometry. Here, we put the emphasis on the challenges of operating integrated optics over a broad wavelength range, a natural condition in the field of Astrophysics. We report on the recent advancements made in obtaining high interferometric contrast (> 90%) through 2-telescope combiners in the mid-IR and give an outlook on more advanced functions and 4-telescope combiners.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Astrophotonics; Integrated optics; Interferometry; mid-IR; Waveguide